2021
DOI: 10.1186/s12887-021-02916-5
|View full text |Cite
|
Sign up to set email alerts
|

How effective is fine motor training in children with ADHD? A scoping review

Abstract: Background Motor deficiencies are observed in a large number of children with ADHD. Especially fine motor impairments can lead to academic underachievement, low self-esteem and frustration in affected children. Despite these far-reaching consequences, fine motor deficiencies have remained widely undertreated in the ADHD population. The aim of this review was to systematically map the evidence on existing training programs for remediating fine motor impairments in children with ADHD and to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 103 publications
1
9
0
Order By: Relevance
“…Some of the benefits obtained from the ludo game are training children's patience in waiting their turn, practicing solving simple problems, and honing skills in socializing with friends (Sikhah, 2018). These benefits are in accordance with the explanation that ADHD children need alternating play activities, channeling energy, as well as activities such as developing strategies and adjusting points on the dice with the number of steps that must be taken in the game in order to reduce frustration, hyperactive and impulsive behavior and train concentration (Afifah et al, 2019 ;Lelong et al, 2021).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Some of the benefits obtained from the ludo game are training children's patience in waiting their turn, practicing solving simple problems, and honing skills in socializing with friends (Sikhah, 2018). These benefits are in accordance with the explanation that ADHD children need alternating play activities, channeling energy, as well as activities such as developing strategies and adjusting points on the dice with the number of steps that must be taken in the game in order to reduce frustration, hyperactive and impulsive behavior and train concentration (Afifah et al, 2019 ;Lelong et al, 2021).…”
Section: Introductionsupporting
confidence: 79%
“…The National Survey of Children's Health (NSCH) in the United States in 2016 explained that 6.1 million children who had been diagnosed with ADHD aged 2-17 years old, 2.4 million aged 6-11 years old, and 12-17 years old were 3.3 million (Bitta et al, 2017). In China it reached 6.26% (Lelong et al, 2021). In Indonesia it is 2.2% for the hyperactivity-impulsivity type, 5.3% for the mixed type of hyperactivity-impulsivity and inattention, and 15.3% for the inattentive type (Utami et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that 50 to 70% of ADHD children demonstrate disturbances in their handwriting legibility and speed [21][22][23][24]. A greater variability; slowness of writing; poor rhythm and flow of writing; poor organization of the written material; poor alignment; poor overall legibility; pronounced variability in the spatial components; poor spacing within and between words; poorly formed letters; inconsistent letter size and shape; letter omissions, insertions, inversions or substitutions; and frequent omissions of words or frequent erasures have all been reported (see [23,25,26]). However, when examining these studies more in detail, it becomes apparent that they provide unclear or even discordant results.…”
Section: Handwriting Deficits In Adhdmentioning
confidence: 99%
“…Therefore we expect that GM are similarly fluent, fast and forceful under methylphenidate than before treatment. Assuming that the physiotherapeutic treatment of the present study (specifically designed to treat and train children's fine and gross motor skills as well as tactile/vestibular/proprioceptive perception) leads to improvements in gross and fine motor skills [26][27][28][29], we expect that GM in both everyday handwriting tasks and in the four basic drawing tasks (two open-eye and two closed-eye drawing tasks) will be more fluent (i.e., lower NIV values) and less forceful (lower pen pressure) but slower (i.e., lower frequencies) due to a trade-off between velocity and legibility [30] after week 8 of treatment than before treatment. As the parental education group did not involve direct treatment of the children, it was treated as a control group for which we do not expect any treatment effects.…”
Section: Introductionmentioning
confidence: 96%